2010
DOI: 10.1101/gad.1934210
|View full text |Cite
|
Sign up to set email alerts
|

A genetic screen identifies the Triple T complex required for DNA damage signaling and ATM and ATR stability

Abstract: In response to DNA damage, cells activate a complex signal transduction network called the DNA damage response (DDR). To enhance our current understanding of the DDR network, we performed a genome-wide RNAi screen to identify genes required for resistance to ionizing radiation (IR). Along with a number of known DDR genes, we discovered a large set of novel genes whose depletion leads to cellular sensitivity to IR. Here we describe TTI1 (Tel two-interacting protein 1) and TTI2 as highly conserved regulators of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
254
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(269 citation statements)
references
References 42 publications
12
254
1
2
Order By: Relevance
“…Genome instability also occurs in clk-2 mutant germlines, but strong alleles lead to a late G2-like cell cycle arrest. Subsequent studies on mammalian and yeast CLK-2 orthologs, referred to as TEL2 in yeasts, established that CLK-2/TEL2 is required for the full activation of all PIKKs-type protein kinases, a class of protein kinases that includes ATM/ atm-1 and ATL-1, thus explaining checkpoint-signalling phenotypes (Hayashi et al 2007 ;Kanoh and Yanagida 2007 ;Hurov et al 2010 ;Takai et al 2010 ;Kaizuka et al 2010 ) . The current model suggests that CLK-2/TEL2 might have a chaperonlike function required for the full activation of those kinases (Horejsi et al 2010 ) .…”
Section: Upstream Dna Damage Checkpoint Signalling In the C Elegans mentioning
confidence: 99%
“…Genome instability also occurs in clk-2 mutant germlines, but strong alleles lead to a late G2-like cell cycle arrest. Subsequent studies on mammalian and yeast CLK-2 orthologs, referred to as TEL2 in yeasts, established that CLK-2/TEL2 is required for the full activation of all PIKKs-type protein kinases, a class of protein kinases that includes ATM/ atm-1 and ATL-1, thus explaining checkpoint-signalling phenotypes (Hayashi et al 2007 ;Kanoh and Yanagida 2007 ;Hurov et al 2010 ;Takai et al 2010 ;Kaizuka et al 2010 ) . The current model suggests that CLK-2/TEL2 might have a chaperonlike function required for the full activation of those kinases (Horejsi et al 2010 ) .…”
Section: Upstream Dna Damage Checkpoint Signalling In the C Elegans mentioning
confidence: 99%
“…The evidence suggesting a role for FUS in DNA repair is particularly intriguing for ALS pathogenesis, given growing evidence that RNA binding proteins are active in the prevention and repair of transcription-associated DNA damage (8)(9)(10)(11)(12). Other ALS-related RNAbinding proteins like SETX, EWSR1, and TAF15 have also been linked to DNA damage and repair, further suggesting the importance of a breakdown in this process in ALS pathogenesis (11,(13)(14)(15)(16).…”
Section: Dna Damage Response | Als | Transcription | R Loopmentioning
confidence: 99%
“…57 Recent studies have also reported that TEL2 forms a 2-MDa complex with TTI1, TTI2, and Hsp90 chaperones, which is required for PIKK stability. 58,59 These studies indicate that TEL2 interacts with newly synthesized PIKKs and does not associate efficiently with the activated, mature form of ATM. Another group also reported that the (AAA+) family proteins RuvB-like 1 (RUVBL1) and RUVBL2 control PIKK abundance at least at the mRNA level, and also form a complex with Hsp90.…”
mentioning
confidence: 97%